2009
DOI: 10.1088/0953-8984/21/34/345801
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the relaxation time distribution underlying the Kohlrausch–Williams–Watts photoionization of the DX centers in Cd1−xMnxTe mixed crystals

Abstract: In this paper we clarify the relationship between the relaxation rate and relaxation time distributions underlying the Kohlrausch-Williams-Watts (KWW) photoconductivity build-ups in indium- and gallium-doped Cd(1-x)Mn(x)Te mixed crystals. We discuss the role of asymptotic properties of the corresponding probability density functions. We show that the relaxation rate distribution, as a completely asymmetric α-stable distribution, leads to an infinite mean value of the effective relaxation rate. In contrast, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…They have an almost equal crossing time t ≈ 1 s. Also, it is observed that of these three derivatives, the derivative of Atangana-Baleanu could describe a wider class of physical processes, becuase it is described in terms of Mittag-Leffler function. Finally, the conformable derivative gives as a solution the stretched exponential behavior, the crossing time is t conf ≈ 3 s. This behavior has been observed in a large number of complex physical processes [53][54][55][56][57][58][59]. Similar behaviors are observed in the case of alternating current AC, Figs.…”
Section: Comparisonsupporting
confidence: 67%
See 2 more Smart Citations
“…They have an almost equal crossing time t ≈ 1 s. Also, it is observed that of these three derivatives, the derivative of Atangana-Baleanu could describe a wider class of physical processes, becuase it is described in terms of Mittag-Leffler function. Finally, the conformable derivative gives as a solution the stretched exponential behavior, the crossing time is t conf ≈ 3 s. This behavior has been observed in a large number of complex physical processes [53][54][55][56][57][58][59]. Similar behaviors are observed in the case of alternating current AC, Figs.…”
Section: Comparisonsupporting
confidence: 67%
“…This derivative is a natural extension of the ordinary derivative, as a limit, and has the same properties as the ordinary one. This derivative can describe phenomena, such as relaxation processes in complex systems and so on [53][54][55][56][57][58]. As far as we know, the conformable derivative had not been applied to the RC circuit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first derivative diverges when t → 0 for any β < 1. In addition, the corresponding response function expressed by the negative time derivative of g(t) exhibits short-time power-law properties and decays stretchedexponentially for long time [146] (see also [128]), namely…”
Section: Kohlrausch Function:properties and Approximationsmentioning
confidence: 99%
“…The KWW functional has been successfully applied to many out-ofequilibrium systems, with an anticorrelation between the disorder and β. 47,48 The fitting coefficients for a KWW analysis of the averaged piezoresponse over time for each composition and voltage are reported in Figs S4-S9 in the Supplementary Information (Figs S4 and S5 plot PMN's response to positive and negative applied voltages, respectively, Figs S6 and S7 plot PMN-0.36PT's response to positive and negative applied voltages, respectively; and Figs S8 and S9 plot PMN-0.40PT's response to positive and negative applied voltages, respectively). However, while such an approach benefits from the reduced statistical noise due to spatial averaging, it results in a loss of any spatial information and therefore possible local chemical heterogeneities.…”
Section: Discussionmentioning
confidence: 99%